Utilization of pumpkin (Cucurbita moschata) seed in broiler chicken diets - Mart?nez, Y.; Valdivi?, Manuel; Estarr?n, M.; C?rdoba, J. (Cuban Journal of Agricultural Science, 2010)
In order to use pumpkin seed meal (PSM) in broiler chicken feeding in Cuba, as partial substitute of soybean cake and imported plant oil, 120 Cobb-500chicks, of one day of age were used. During 49 d, they were allotted according to completely randomized design into two treatments and three repetitions. The treatments consisted of diets, with levels of inclusion of 0 and 10 % of pumpkin seed meal. No significant differences were observed between treatments the viability (95 %), final liveweight (2268 and 2265 g/bird), feed intake (4837 y 4831 g/bird), feed conversion (2.13), carcass weight (1634 and 1625 g/bird), breast yield (23.73 and 23.52 %) and weight of thigh + leg (511 and 519 g/bird). The excessive abdominal fat diminished with the inclusion of 10 % pumpkin seed meal. No differences were observed in the sensorial quality of the meat from the breast and thigh. The results obtained suggested the utilization up to 10 % of pumpkin seed meal in broiler chicken diets, not changing the productive performance and the sensorial quality of the meat. Key words: seed, pumpkin, chicken.